Brood care behavior of the painted stork (Mycteria leucocephala) in Peninsular Malaysia - Mohd Amir Zakaria; Ummi Nur Syafiqah Daud; Mohammad Saiful Mansor; Shukor Md. Nor (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Zakaria MA, Daud UNS, Mansor MS, Md. Nor S. 2022. Brood care behavior of the painted stork (Mycteria leucocephala) in Peninsular Malaysia. Biodiversitas 23: 5406-5411. Waterbirds can serve as bio-indicators for their surrounding environments, indicating issues such as habitat degradation and climate change. One factor that contributes to successful reproduction for many bird species is parental behavior during the brood care stage. The painted stork (Mycteria leucocephala) is a waterbird species that provide biparental care throughout the breeding season. Although many studies have focused on populations of this species, information about their behavior, particularly during nestling rearing, remains lacking. Hence, this study was conducted to examine the parental behavior of painted storks between the early and late stages of brood care in two different colonies located in Peninsular Malaysia: Tasik Shah Alam (TSA) in Selangor and Upper Bisa Putrajaya Wetland (UBPW) in Putrajaya from May to September 2016. Three pairs of painted storks were monitored in every site, and seven behaviors were identified: roosting, preening, nest repair, wing opening, flying, feeding and brooding. Of all the behaviors recorded, flying, roosting and wing-opening behavior were the most frequently observed behaviors in both study areas during the early stage of brood care. However, painted storks were found to spend most of their time flying when the chicks had grown up by the late stage. This may be due to the food demand for the parents and their chicks. As the nestlings grow bigger, more food is required before the nestling can fledge independently. This is supported by increased feeding frequency observed from the early to late stages. Males were found to have a higher frequency of all behaviors than females. This data facilitates a greater understanding of painted stork behavior, which can help in their conservation and management processes.